DANA ALOKASI UMUM, DANA BAGI HASIL, DANA ALOKASI KHUSUS DAN PENDAPATAN ASLI DAERAH PROVINSI BALI - Putra, Ida Bagus Dwi; Dwirandra, A. A. N.B. (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
This study was conducted to determine the influence of the General Allocation Fund, Sharing Funds, Special Allocation Fund and Regional Income in Local Expenditure as well as to confirm the occurrence of the phenomenon of flypaper in the government's financial district / city in the province of Bali. This research was conducted in budget year 2005-2012, using secondary data. The analysis technique used was multiple linear regression . The results of this study found that the general allocation fund, sharingfunds and local revenue positive and significantly effect on regional spending, while the Special Allocation Fund was not a significantly positive effect on regional spending. There was not Flypaper phenomenon in local department of Bali province proved by regression coefisiens of general funds that smaller then those of local own revenue. Normal 0 false false false EN-US X-NONE X-NONE Normal 0 false false false EN-US X-NONE X-NONE Normal 0 false false false EN-US X-NONE X-NONE This study was conducted to determine the influence of the General Allocation Fund, Sharing Funds, Special Allocation Fund and Regional Income in Local Expenditure   as well as to confirm the occurrence of the phenomenon of flypaper in the government's financial district / city in the province of Bali. This research was conducted in budget year 2005-2012, using secondary data. The analysis technique used was multiple linear regression . The results of this study found that the general allocation fund, sharingfunds and local revenue positive and significantly effect on regional spending, while the Special Allocation Fund was not a significantly positive effect on regional spending. There was not Flypaper phenomenon in local department of Bali province   proved by regression coefisiens of general funds that smaller then those of local own revenue. Normal 0 false false false EN-US X-NONE X-NONE
Keywords: General Allocation Fund, Sharing Funds, Special Allocation Fund, Local Revenue, Regional Spending